A Significant Increase of RNAi Efficiency in Human Cells by the CMV Enhancer with a tRNAlys Promoter. (16th September 2009) - Weiwei, Ma; Zhenhua, Xie; Feng, Liu; Hang, Ning; Yuyang, Jiang
Abstract : RNA interference (RNAi) is the process of mRNA degradation induced by double-stranded RNA in a sequence-specific manner. Different types of promoters, such as U6, H1, tRNA, and CMV, have been used to control the inhibitory effect of RNAi expression vectors. In the present study, we constructed two shRNA expression vectors, respectively, controlled bytRNA lys and CMV enhancer-tRNA lys promoters. Compared to the vectors withtRNA lys or U6 promoter, the vector with a CMV enhancer-tRNA lys promoter silenced pokemon more efficiently on both the mRNA and the protein levels. Meanwhile, the silencing of pokemon inhibited the proliferation of MCF7 cells, but the induction of apoptosis of MCF7 cells was not observed. We conclude that the CMV enhancer-tRNA lys promoter may be a powerful tool in driving intracellular expression of shRNA which can efficiently silence targeted gene.